2014
DOI: 10.1111/jgs.13082
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Levels and Cognition in Elderly Adults in China

Abstract: Objectives To evaluate the association between vitamin D status and cognitive impairment (CI) in elderly aged 60 years and above Design Cross-sectional cohort study Setting Chinese Longitudinal Healthy Longevity Survey, a community-based cohort study in longevity areas in China Participants Individuals with mean age of 84.9 (± 12.7) (n=2004) Measurements Participants’ cognitive state was evaluated using the Mini-Mental State Examination (MMSE). Vitamin D in plasma was measured using enzyme-linked immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 30 publications
2
43
0
3
Order By: Relevance
“…Serum 25(OH)D 3 concentration is correlated with regional cerebral blood flow (Farid et al., ), brain volume and gray matter thickness (Brouwer‐Brolsma et al., ; Buell et al., ; Hooshmand, Lökk, & Solomon, ) and clearance of aggregated Aβ in the AD brain (Durk et al., ; Masoumi, Goldenson, & Ghirmai, ; Yu et al., ). On the other hand, low serum 25(OH)D 3 is associated with neuronal damages (Gezen‐AK, Yilmazer, & Dursun, ), MCI (Annweiler et al., ), multidomain MCI (Yin et al., ) and AD (Annweiler et al., ; Balion, Griffith, & Strifler, ; Chei et al., ; Littlejohns, Henley, & Lang, ). The present results showed that 25(OH)D 3 is involved in the decrease of MMSE, and predict MCI, mild AD, and moderate AD.…”
Section: Discussionmentioning
confidence: 99%
“…Serum 25(OH)D 3 concentration is correlated with regional cerebral blood flow (Farid et al., ), brain volume and gray matter thickness (Brouwer‐Brolsma et al., ; Buell et al., ; Hooshmand, Lökk, & Solomon, ) and clearance of aggregated Aβ in the AD brain (Durk et al., ; Masoumi, Goldenson, & Ghirmai, ; Yu et al., ). On the other hand, low serum 25(OH)D 3 is associated with neuronal damages (Gezen‐AK, Yilmazer, & Dursun, ), MCI (Annweiler et al., ), multidomain MCI (Yin et al., ) and AD (Annweiler et al., ; Balion, Griffith, & Strifler, ; Chei et al., ; Littlejohns, Henley, & Lang, ). The present results showed that 25(OH)D 3 is involved in the decrease of MMSE, and predict MCI, mild AD, and moderate AD.…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin D status is related to many types of health outcomes among the elderly population and can contribute to musculoskeletal complications (including proximal myopathy, bone and muscle pain, secondary hyperparathyroidism, osteoporosis, and osteomalacia) [1], chronic diseases (cancer and cardiovascular diseases) [2], autoimmune diseases (systemic lupus erythematosus, multiple sclerosis, scleroderma or systemic sclerosis, autoimmune thyroid diseases, rheumatoid arthritis and primary biliary cirrhosis) [3, 4], and psychotic disorders (depression, self-neglect and cognitive impairment) [57]. All these diseases can cause disability among the elderly.…”
Section: Introductionmentioning
confidence: 99%
“…Vitamin D has shown direct protective effects against neurotoxic insults in vitro , and played an important role in neurotrophic factors in vivo . In addition, several cross‐sectional or longitudinal studies have reported the association of vitamin D deficiency and cognitive impairment . However, not all studies have shown this association …”
Section: Introductionmentioning
confidence: 99%